Taxes and subsidies in EU energy policy: Fit for 55? - Claudia Kettner; Eva Wretschitsch (Austrian Institute of Economic Research (WIFO), 2023)
In the "Fit for 55" package of July 2021, the European Commission proposed inter alia a revision of the energy taxation directive with the intent of increasing tax rates for fossil fuels that should contribute to achieving the EU's emission reduction targets for 2030. Since then, climate policy challenges in the EU have been amplified by sharp increases in electricity and gas prices mainly as a result of the war in Ukraine. Energy price spikes have led to the implementation of numerous compensation measures for households and firms in EU member countries. In this article, we provide an overview of the discussion on energy taxation in the EU and analyse compensation measures implemented during the energy crisis. We find that energy cost related compensation measures counter climate policy efforts. A stronger focus on vulnerable groups would have reduced the overall costs of measures and entailed stronger energy efficiency incentives.
Keywords: 330; EU; energy taxation; energy cost subsidies; energy crisis